Tingkat Retensi Protein dan Retensi Lemak Yang Berbeda Terhdap Pertumbuhan Ikan Betutu (Oxyeleotris marmorata) - Wiradana, Muhammad Syafrani; Almadi, Ismail Fahmy; Sukarti, Komsanah (Universitas Batangahari Jambi, 2024)
This study aims to examine the growth of weight, length and specific growth rate, analyze protein retention and fat retention in marbel gooby fed with different live feed. This study used a completely randomized design with 3 treatments and 5 replications, namely; P1 live feeding in the form of tilapia fry; P2 live feeding in the form of freshwater shrimp; P3 live feeding in the form of thousand fish. The feeding method is done in the morning and night. The results of the analysis of variance of the treatment of differences in live feeding on marbel goby were not significantly different from absolute weight growth, total length growth, specific growth rate, feed conversion and protein efficiency ratio. On live feed, thousand fish showed the highest growth value in absolute weight, total length, specific growth rate (P>0.05). The results of the analysis of variance of the treatment of differences in live feeding on marbel goby were not significantly different from protein retention and significantly different from fat retention of marbel goby (P <0.05).Â